Mantra Pesisir (Pertemuan Tradisi dan “Ilmu” Masyarakat Islam Pesisir) - Hariansyah Hariansyah (AT-TURATS, 2017)
Spells illustrating language power able to influence even to dominate souls. This article shows that human psychology (traditionally seashore community or cosmopolitan community) basically hard to self release from spells and supertition world? Is spell and supertition world forms of human psychology primordial characteristic? Psychology explanation about magic practice cause existence and spells more certainty because the effectiveness of charms that spells promised. It description towards bibliography study methods and narration analysis. Narrative analysis making flashback after construction theme, investigating social background and fighting ideas domination to draw dominant value, giving hidden intention from ideas (text) and reflecting continuity and review ideas on text, next reconstructing and narating to become complete story until become ideology.